(untitled) (Revista Argentina de Musicología, 2018)
The present text deals with some of the essential points concerning the notion of musical and musicological canons, their mechanisms of formation. their modes of apparition and action. It considers the discussion about some of the opposed concepts of the canon. There are those who conceive it as a settled expression of the esthetic and historic experience of a society, and those who identify it as one of the ways the hegemonic classes and groups exercise their power on the excluded Others. in order to impose their cultural and ideological paradigms. The text refers to the canon as a theoretical problem for the discipline and in particular to the questions rai sed by our study in our own contexts and conditions of study and of production.